Physical activity promotion among pregnancy – the role of physician from the women’s perspective - Laudańska-Krzemińska, Ida; Krzysztoszek, Jana (Frontiers in Public Health, 2024)
Objective The clear benefits of planned and supervised physical activity (PA) during pregnancy make it imperative that women are encouraged and educated about this activity. This study aimed to investigate how effectively physician promote physical activity and exercise among pregnant women. It also examines pro-health changes in selected health behaviours during pregnancy. Methods This cross-sectional study recruited a total of 353 pregnant women in Wielkopolskie Voivodship in Poland. An anonymous survey (on-line or in-paper) was used to assess physical activity before and during pregnancy (with Pregnancy Physical Activity Questionnaire), physical activity self-efficacy, well-being (WHO-5 Well-Being Index), and guidance received from physicians on physical activity during pregnancy. Results Only 41% of women surveyed followed WHO recommendations for PA before pregnancy, and they were much more likely to discuss safety and the need to change the intensity or type of PA with their doctor or gynaecologist. Only 23% of women were asked about their PA before pregnancy and less than 40% were encouraged to be active during pregnancy. We observed a higher probability of poor well-being among pregnant women who were inactive before pregnancy (OR = 1.873, 95%CI 1.026 to 3.421, p = 0.041). Conclusion Health professionals infrequently educate and motivate women to be physically active during pregnancy. Physician advice, as it is currently perceived by women, seems to be insufficient to help pregnant women meet the recommendations for PA during pregnancy.